Transactional Leadership in Educational Institutions in the Perspective of Islamic Economic Law - Soro, Suharyanto H; Sunarya, Fitri R. (SALAM: Jurnal Sosial dan Budaya Syar-i, 2024)
Transactional leadership is a managerial strategy that emphasizes the reciprocal dynamics between leaders and followers through rewards and punishments, aimed at efficiently achieving corporate objectives in a systematic manner. Within educational institutions, implementing transactional leadership may enhance the discipline and performance of followers; however, it requires additional examination within the context of Islamic economic law. This study examines the implementation of transactional leadership inside educational institutions via the lens of Islamic economic law and assesses its influence on institutional performance. This study employs a qualitative methodology via a literature review to analyze diverse sources pertaining to transactional leadership and Islamic economic law. The study's findings suggest that transactional leadership in educational institutions can be implemented by adapting sharia principles, including equity, transparency, and a balance between rewards and penalties. Academic institutions must adopt a more comprehensive and motivating strategy to foster a more inventive and significant environment for stakeholders.Keywords: Transactional Leadership; Educational Institutions; Islamic Economic Law AbstrakKepemimpinan transaksional merupakan strategi manajerial yang menekankan dinamika timbal balik antara pemimpin dan pengikut melalui penghargaan dan hukuman, yang ditujukan untuk mencapai tujuan perusahaan secara efisien dan sistematis. Dalam lembaga pendidikan, penerapan kepemimpinan transaksional dapat meningkatkan disiplin dan kinerja pengikut; namun, hal ini memerlukan pemeriksaan tambahan dalam konteks hukum ekonomi Islam. Studi ini mengkaji penerapan kepemimpinan transaksional di dalam lembaga pendidikan melalui sudut pandang hukum ekonomi Islam dan menilai pengaruhnya terhadap kinerja kelembagaan. Studi ini menggunakan metodologi kualitatif melalui tinjauan pustaka untuk menganalisis berbagai sumber yang berkaitan dengan kepemimpinan transaksional dan hukum ekonomi Islam. Temuan studi ini menunjukkan bahwa kepemimpinan transaksional di lembaga pendidikan dapat diterapkan dengan mengadaptasi prinsip-prinsip syariah, termasuk ekuitas, transparansi, dan keseimbangan antara penghargaan dan hukuman. Lembaga pendidikan harus mengadopsi strategi yang lebih komprehensif dan memotivasi untuk menumbuhkan lingkungan yang lebih inventif dan signifikan bagi para pemangku kepentingan.Kata Kunci: Kepemimpinan Transaksional; Lembaga Pendidikan; Hukum Ekonomi Syariah